Criminal Disparity in Decisions in Cases of Theft With Violence in the Demak District Court - Suudi, Ali (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Article 37 paragraph (1) of PP No. 24 of 1997 requires that land sales and purchases must be proven by a deed from a PPAT. However, in Demak Regency, the practice of buying and selling land underhand is still common without an authentic deed, thus complicating the initial land registration process. This study uses a juridical-sociological approach and aims to examine the implementation and obstacles of land registration due to underhand sales in Demak Regency. The results show that although land registration requirements are formally regulated, people often only have unofficial evidence such as receipts or statements. This results in land registration applications being rejected due to not meeting legal requirements. The proposed solution is the need for special regulations to accommodate underhand sales and increased legal education so that the public understands the importance of authentic deeds for legal certainty over land.Keywords: Buying and Selling; First Time; Land Registration; Under Hand.